Knee Septic arthritis due to Serratia marcescens in a patient with hemophylia A - Montoya-Reátegui, Adriana (2023)
We present the case of a 24-year-old male patient with hemophilia A of 14 years of evolution. The patient presented recurrent hemarthrosis in the right knee, who developed septic arthritis in knee due to Serratia marcescens with a satisfactory response to intra-articular lavage with saline solution and 28 days of treatment whith carbapenems. In patients with septic arthritis, previous hemarthrosis and multiple hospital admissions, the presence of this germ should be suspected. The treatment is surgical and with broad-spectrum antibiotics.